The Future of Inequality - Wallerstein, Immanuel (Hagar: Studies in Society and Culture, 2001)
The article discusses about the future of inequalities. The author claimed that this entire discussion, one can see that equality has been an unpopular concept. He analyzes on the origin and the reality of existing inequalities, stating that realism only enters oftentimes in the picture, because it seems to be greatly on the side of maintaining inequalities. He answers the question on what has social science had to assert about inequality in the modern world, and has it been in any place near right. Moreover, he discussed the political, economic, and social concessions and their relationship towards inequality.